2012
DOI: 10.1016/j.nut.2011.12.014
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of anthropometric measurements in estimating fat mass in individuals with 21-hydroxylase deficiency

Abstract: In children and adolescents with 21OHD, %BF as estimated by skinfold measurements was associated more strongly with DXA-assessed %BF than both BMI and WC. However, still, the skinfold-based assessment underestimated DXA %BF and showed moderate agreement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 36 publications
0
8
0
1
Order By: Relevance
“…However, it is also subject to propagation of measurement errors, is time consuming, and requires sophisticated and highly specialized technical equipment. Moreover, it is restricted to research facilities and has high costs, making it difficult to use in large samples [ 37 ]. Nevertheless, DXA has been used by various researchers to develop pediatric equations [ 19 , 38 41 ], therefore considered as a valid and reliable method [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, it is also subject to propagation of measurement errors, is time consuming, and requires sophisticated and highly specialized technical equipment. Moreover, it is restricted to research facilities and has high costs, making it difficult to use in large samples [ 37 ]. Nevertheless, DXA has been used by various researchers to develop pediatric equations [ 19 , 38 41 ], therefore considered as a valid and reliable method [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…A four-compartment model (4C model) is actually the most strong model for accurately assesses body composition in children as it accounts for the variability of the main FFM components [31]. Though its use is recommended as criterion, this method is time-consuming and requires sophisticated equipment, specialized technicians, and high costs which make it difficult for use in large samples [32]. In addition, the 4C model is not free of errors, considering the number of required techniques necessary for determining the main FFM constituents (water and mineral) [8].…”
Section: Discussionmentioning
confidence: 99%
“…Historically, large cohort studies and national surveys have relied on relatively inexpensive and generally reliable anthropometric measures, such as weight, height, waist circumference and skinfold measures, to estimate body composition in children and adults (12)(13)(14)(15) . However, these methods are generally not generalisable and may create biased estimates especially when body composition compartments, such as percentage body fat, have been calculated using prediction equations developed from populations that differ by age, race and/or ethnicity (16)(17)(18)(19)(20)(21) . For example, Hoffman et al (15) reported that skinfold prediction equations consistently underestimated body fat mass (FM) compared with dual-energy X-ray absorptiometry (DXA) and 2 H dilution.…”
mentioning
confidence: 99%